PROTECTION OF INDIGENOUS LAW COMMUNITIES THROUGH THE REGULATION OF ULAYAT LAND REGISTRATION IN INDONESIA - Wahyudi Saputro; Muhammad Hatta Roma Tampubolon; Ansar Ansar (PRANATA HUKUM, 2026)
This legal research employs a socio-legal methodology, incorporating statutory, conceptual, and comparative approaches. The study aims to critically examine the regulatory framework governing the registration of ulayat land in Indonesia and to construct a regulatory model capable of providing effective protection for Indigenous Law Communities. The findings indicate that the current regulatory scheme for ulayat land registration is fragmented across several authorities: local governments are authorized to designate the subjects, the Ministry of Forestry determines the object in relation to the legal status of customary forests, and the Ministry of Agrarian Affairs and Spatial Planning/National Land Agency determines the object in relation to ulayat land. This model is inconsistent with the holistic concept of customary territories, in which territory and its Indigenous community constitute an inseparable unity. Such a fragmented regulatory structure creates layered and repetitive administrative procedures, thereby hindering Indigenous Law Communities from obtaining adequate legal protection. To ensure meaningful protection, the study argues that a unified regulatory model is required—one that integrates the recognition and protection of Indigenous Law Communities (as legal subjects) with the recognition and protection of customary territories (as legal objects) under the authority of local government. This model would involve coordination with the land office, the forest area consolidation agency, and relevant vertical institutions within a formal Indigenous Law Community Committee. Every decision recognizing and protecting an Indigenous Law Community must be followed by the removal of customary territories from forest areas/state forests when such territories fall within forest zones, or by the demarcation and separation of customary territories from Other Land Uses (APL) when located within APL zones.